2014
DOI: 10.5194/acp-14-7601-2014
|View full text |Cite
|
Sign up to set email alerts
|

The fate of NO<sub>x</sub> emissions due to nocturnal oxidation at high latitudes: 1-D simulations and sensitivity experiments

Abstract: Abstract.The fate of nitrogen oxide pollution during high-latitude winter is controlled by reactions of dinitrogen pentoxide (N 2 O 5 ) and is highly affected by the competition between heterogeneous atmospheric reactions and deposition to the snowpack. MISTRA (MIcrophysical STRAtus), a 1-D photochemical model, simulated an urban pollution plume from Fairbanks, Alaska to investigate this competition of N 2 O 5 reactions and explore sensitivity to model parameters. It was found that dry deposition of N 2 O 5 ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…As urban‐polluted air transports away from the city and mixes with ozone‐rich air, nocturnal nitrogen oxide chemistry becomes active (Apodaca et al, ; Huff et al, ) leading to deposition of nitric acid and particulate nitrate. Joyce et al () considered this chemical‐meteorological coupling for Fairbanks wintertime conditions through use of a 1‐D chemical transport model and found that N 2 O 5 chemistry was suppressed in the urban airshed, which was consistent with the small mass fraction of nitrate in urban Fairbanks particulate matter, but occurred aloft and downwind and was a strong function of available ammonia, affecting the regional fate of the pollution. In regions where more vertical mixing occurs, such as in the midlatitude city of Salt Lake City, Utah, this mixing may bring ammonium nitrate formed aloft back down to impact breathing‐level air quality, which is consistent with the large fraction of ammonium nitrate in Utah wintertime particulate matter.…”
Section: Air Pollution Chemistry Under Arctic Conditionsmentioning
confidence: 98%
See 2 more Smart Citations
“…As urban‐polluted air transports away from the city and mixes with ozone‐rich air, nocturnal nitrogen oxide chemistry becomes active (Apodaca et al, ; Huff et al, ) leading to deposition of nitric acid and particulate nitrate. Joyce et al () considered this chemical‐meteorological coupling for Fairbanks wintertime conditions through use of a 1‐D chemical transport model and found that N 2 O 5 chemistry was suppressed in the urban airshed, which was consistent with the small mass fraction of nitrate in urban Fairbanks particulate matter, but occurred aloft and downwind and was a strong function of available ammonia, affecting the regional fate of the pollution. In regions where more vertical mixing occurs, such as in the midlatitude city of Salt Lake City, Utah, this mixing may bring ammonium nitrate formed aloft back down to impact breathing‐level air quality, which is consistent with the large fraction of ammonium nitrate in Utah wintertime particulate matter.…”
Section: Air Pollution Chemistry Under Arctic Conditionsmentioning
confidence: 98%
“…However, BVOC emissions have been poorly characterized in the boreal regions and the Arctic. Measurements have generally focused on European boreal forests with a major emphasis on monoterpenes (Bäck et al, 2012;Juráň et al, 2017;Rantala et al, 2015;Spirig et al, 2004;Zhou et al, 2017). Coniferous tree species characteristic of the boreal forests are efficient monoterpene emitters (Rinne, Tuovinen, et al, 2000), which leads to larger monoterpene/isoprene emission ratios in the boreal regions compared with forest ecosystems at lower latitudes (Guenther et al, 2012).…”
Section: Natural Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be pointed out that our model only represents the situation at the measurement height of HONO and the supporting species (5 m) and is not used to attempt to describe the entire BL. Numerous measurements demonstrate that near-surface vertical structure in HONO can be significant at night and during the day (Stutz et al, 2002;Kleffmann et al, 2003;Kleffmann, 2007;Zhang et al, 2009;Villena et al, 2011;Wong et al, 2012;Young et al, 2012;Oswald et al, 2015) and that a model using a near-surface source distributed throughout the BL produces results inconsistent with observations (Vandenboer et al, 2013;Wong et al, 2013;Kim et al, 2014;Sörgel et al, 2015). Thus, some of the discrepancy between the model and measurements, particularly in the early morning when thermal inversions can persist, could be ascribed to biases from vertical stratification in HONO.…”
Section: Missing Hono Sourcementioning
confidence: 99%
“…The time series of temperature profiles are constructed following the same procedure as used in the construction of O 3 profiles, comprising the radiosonde temperature profiles (from the surface to 25 km) merged with NCEP/NCAR reanalyses (Kalnay et al, 1996) temperatures used in the retrieval of MOPI1 ozone (above 25 km) for the period of 1994-2010. From near the stratopause upwards the NCEP/NCAR temperatures are merged with a mesospheric climatology based on local lidar measurements.…”
Section: The Single-column Photochemical Model (Scm)mentioning
confidence: 99%